Changes in phenolic compound profiles and antioxidant activity of peanut (Arachis hypogaea L.) as affected by roasting and storage conditions - Win, Mar Mar (2011)
Peanut (Arachis hypogaea L.) has been recognised as a functional food because of the presence of numerous phytochemicals with antioxidant capacity. In this study, peanut skin, hull, raw peanut and roasted peanut flour were analysed for their contents of total phenols, antioxidant activity and individual phenolic composition. The effect of different roasting times (0, 10, 20, 30, 40, 50 min at 160 ˚C) of peanut flour (with and without skin) on phenolic compounds and their antioxidant activity were evaluated. Changes of phenolic composition and antioxidant activity were also monitored during storage of roasted peanut flour at 5, 25, and 37˚C for 0, 15, 30, 45 and 60 days. Results of the study showed that peanut skin had a significantly (p < 0.05) higher total phenolic compounds (TPC) and exhibited higher antioxidant activity than that of hulls, roasted peanut flour, and raw peanut as measured by DPPH, Linoleic acid peroxidation and TBA method, confirming the fact that phenolic compounds in peanuts are largely concentrated in the skins. Interestingly, as increasing roasting times, TPC and antioxidant capacity of peanut flour with and without skin, were significantly (p < 0.05) increased in a time dependent manner. Results of HPLC analysis revealed that the concentration of p-coumaric acid and quercetin in peanut flour with skin significantly (P < 0.05) increased after 30, 40, and 50 min of roasting. However, most of the phenolic compounds in peanut flour without skin, decreased gradually after 20 min of roasting time. Changes in TPC of roasted peanut flour without skin were independent of storage time and temperature, but antioxidant activity was found to be quite stable when stored at 5 ˚C. Individual phenolic compounds of roasted peanut flour without skin were significantly increased at the end of storage. After 45 days of storage, the levels of TPC of roasted peanut flour with skin significantly increased at all storage temperatures. However, antioxidant activity did not change significantly during storage. Surprisingly, individual phenolic compositions of roasted peanut flour with skin were found to be unstable and degraded at the end of storage (60 days). In conclusion, this study revealed that roasted peanut flour can be used as functional food ingredient with excellent sources of natural antioxidant compounds when appropriate processing and storage conditions are applied.